Randomized controlled trial of a self-management intervention in persons with spinal cord injury: design of the HABITS (Healthy Active Behavioural IntervenTion in SCI) study. (June 2013) - Kooijmans, H.; Post, M. W. M.; van der Woude, L. H. V.; de Groot, S.; Stam, H. J.; Bussmann, J. B. J.
<x xml:space="preserve">Abstract</x> Purpose: To evaluate the effectiveness of a 16-week self-management intervention on physical activity level and self-management skills (self-efficacy, proactive coping and problem solving skills) in persons with chronic SCI. Method and design: Multicenter randomized controlled trial (RCT). Eighty persons with a SCI for at least 10 years and aged 18 to 65 will randomly be assigned to the intervention (self-management) or the control group (information provision). During the 16-week self-management intervention (one home-visit, five group and five individual sessions) active lifestyle will be stimulated and self-management skills will be taught. Data will be collected at baseline (T0), 16 (T1) and 42 (T2) weeks after baseline. Primary outcome measure is level of daily physical activity (self-report/objectively measured). Secondary outcome measures are self-managements skills, stage of behaviour change and attitude. Conclusion: This is the first RCT on self-management in people with chronic spinal cord injury. This trial will provide knowledge on the effects of a self-management intervention on physical active lifestyle in persons with a long-term SCI.